Parental investment in Tibetan populations does not reflect stated cultural norms. (20th October 2017) - Du, Juan; Mace, Ruth
Abstract : The evolutionary processes that generate cultural group norms and individual behavior may differ. We found that stated gender preference is based on the social norm of son preference, whilst real-life biases in parental investment were in favor of daughters. The recent history of the region includes dramatic government policy changes that influenced the behavioral ecology of the system by changing access to resources and inheritance rules. We discuss how male preferences may differ from female preferences; and we discuss how social norms and maternal behavior may be generated by different evolutionary processes. Abstract: In this paper, we examined both stated norms of sex preference and actual sex-biases in parental investment in a Tibetan pastoralist society. We collected detailed demographic data on infant mortality, infant feeding, the length of interbirth intervals, and a decision when giving gifts, to examine sex-biased parental investment. Our results indicate a mismatch between self-reported son preference and measures of actual parental investment that favor daughters. We interpret this female-biased parental investment as a possible response to daughters generating more economic resources. However, the stated sex preferences of both sexes reflect cultural norms that appear to have remained unchanged over a long period, which may reflect the importance of male roles in the past. Our behavioral measures of parental investment are those most likely to be in the control of women (such as breastfeeding and interbirth interval), so this mismatch between stated and actual investment may be especially true of women.